2014
DOI: 10.1111/ap.12056
|View full text |Cite
|
Sign up to set email alerts
|

Working with Older Adults: Predictors of Attitudes Towards Ageing in Psychology and Social Work Students, Faculty, and Practitioners

Abstract: The Australian population is experiencing a rapid ageing of the population, and as such, an increased need for gerontological practitioners in the helping professions will continue to grow. Terror management theory (TMT), which was used to frame this study, posits that because of the fact that humans are aware of their own mortality, they are compelled to avoid the anxiety associated with it. Personal ageing and interaction with older adults may be reminders of the unavoidable decline and death that faces us a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 45 publications
5
42
1
2
Order By: Relevance
“…The results of this study indicated that participants described older adults more positively and their perceptions about working with older adults became more positive following the interprofessional geriatric training experience. This study supports previous findings that educational programs may have the potential to influence ageist attitudes and improve willingness to work with older adults ( Kother, & Weilandt, 2011;Chonody et al, 2014;Horowitz et al, 2014;King et al, 2013;Oggins & Whitlow, 2001;Wilkinson et al, 2002). These findings are important since ageist attitudes and stereotypes have been identified as barriers to being able to recruit occupational therapists to work with older adults (Wilkins & Rosenthal, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study indicated that participants described older adults more positively and their perceptions about working with older adults became more positive following the interprofessional geriatric training experience. This study supports previous findings that educational programs may have the potential to influence ageist attitudes and improve willingness to work with older adults ( Kother, & Weilandt, 2011;Chonody et al, 2014;Horowitz et al, 2014;King et al, 2013;Oggins & Whitlow, 2001;Wilkinson et al, 2002). These findings are important since ageist attitudes and stereotypes have been identified as barriers to being able to recruit occupational therapists to work with older adults (Wilkins & Rosenthal, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Even though the literature suggests there is ageism and decreased desire to work with older adults among healthcare students and workers, there is evidence to suggest that healthcare students who interact with older adults as part of their educational programs are able to maintain better attitudes about aging and are less likely to believe negative stereotypes (Brown, Kother, & Weilandt, 2011;Currey, 2008;Klein & Liu, 2010). In fact, numerous studies have provided evidence that the provision of opportunities for students to work directly with older adults has helped combat ageist beliefs and has positively influenced willingness to work with older adults (Chonody, Webb, Ranzjin, & Bryan, 2014;Horowitz, Tagliarino, & Look, 2014;King, Roberts, & Bowers, 2013;Oggins & Whitlow, 2001;Wilkinson, Gower, & Sainsbury, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these beliefs do influence behavior. Chonody, Webb, et al (2014) found that negative and positive ageisms were significantly correlated and helped explain comfort in spending time with older adults. Allport's (1954) contact theory suggests that exposure to member(s) of an out-group can help improve attitudes toward that group, and past research supports its influence on ageism.…”
Section: Ageisms: Positive and Negative Stereotyping Of Older Adultsmentioning
confidence: 96%
“…However, positive ageism may actually help explain time spent with older adults. In one study, it was found that when positive ageism decreased, participants were less comfortable spending time with older adults (Chonody, Webb, Ranzijn, & Bryan, 2014). Cherry and Palmore (2008) theorize that people perceive these behaviors as ''courteous or thoughtful, and not ageism per se' ' (p. 856).…”
Section: Ageisms: Positive and Negative Stereotyping Of Older Adultsmentioning
confidence: 99%
“…Studies have predominantly explored resistance towards ageing as an attitudinal variable (Adelman, Greene, & Charont, ; Angus & Reeve, ; Berger, ). For example, awareness of one's own mortality is associated with higher levels of anxiety (Chonody, Webb, Ranzijn, & Bryan, ). Additionally, individuals who uphold negative stereotypes and higher levels of anxiety experience greater unease towards the future (Ramírez & Palacios‐Espinosa, ).…”
Section: Attitudes Towards Ageingmentioning
confidence: 99%